Saturated Fatty Acids from Dairy Increase Energy Expenditure Following an Acute Meal Challenge (P08-015-19). (24th October 2019) - Rust, Bret; Casperson, Shanon; Raatz, Susan; Picklo, Matthew
Abstract: Objectives: Evidence suggests that the amount of fatty acid saturation and chain length affect fatty acid oxidation. Metabolism of unsaturated fatty acids may increase energy expenditure and shorter chain fatty acids may be selectively oxidized more readily. More data are needed to determine the impact of fatty acids, as they exist in dietary fats and oils, upon energy expenditure. We tested differences in energy expenditure after an acute meal challenge prepared with dietary fats and oils with fatty acids of differing chain lengths and saturation. The fats and oils used included olive oil (OO, for oleic acid, 18:1n-9), flaxseed oil (FL, for alpha-linolenic acid, 18:3n-3), sunflower oil (SO, for linoleic acid, 18:2n-6), heavy cream (HC, for saturated fatty acids) and fish oil (FO, for docosahexaenoic acid, 22:6n-3). Methods: Healthy men and women (N = 27; 56% men; age: 26.8 ± 6.8; BMI: 29.1 ± 3.2), participated in a five-way crossover trial with intention to treat analysis. Body composition was assessed prior to the first study visit by dual X-ray absorptiometry. A standard three-day lead-in diet, prescribed for the participants' energy needs, was consumed prior to testing. Subjects entered the metabolic chamber the evening before testing and were awakened at 6 AM for a resting metabolic rate measurement followed by a four-hour meal challenge. Test days were separated by at least 7 days. A 500 kcal smoothie with 30 g of test fat source was consumed within 15 min of an initial fasting blood draw. Metabolic rate (MR) and oxidation rates for fat, carbohydrate and protein were analyzed with proprietary software (PiLR™; MEI Research, Ltd.) for four hours after the challenge. Results: MR standardized to fat free mass (FFM) and independent of FFM was greater after HC (1.64 ± 0.24 kcal/min) than FL (1.55 ± 0.26 kcal/min) and OO (1.53 ± 0.24 kcal/min) ( P < 0.01) over the 4 hr postprandial period. Over four hours these differences accounted for 21.6 and 26.4 fewer kcal oxidized, respectively. Substrate oxidation rates did not differ between dietary fats. Conclusions: In contrast to previously reported data, our initial data suggest dairy-derived saturated fatty acids may increase postprandial MR following an acute meal challenge. Funding Sources: This work was supported by USDA-ARS project 3062-51000-053-00D.